2019
DOI: 10.3390/catal9100861
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Optimal Production of Flavonol Aglycones and Degalloylated Catechins from Green Tea Using a Multi-Function Food-Grade Enzyme

Abstract: 1) Background: Green tea (GT) contains well-known phytochemical compounds; namely, it is rich in flavan-3-ols (catechins) and flavonols comprising all glycoside forms. These compounds in GT might show better biological activities after a feasible enzymatic process, and the process on an industrial scale should consider enzyme specificity and cost-effectiveness. (2) Methods: In this study, we evaluated the most effective method for the enzymatic conversion of flavonoids from GT extract. One enzyme derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…The interactions between tannases from LAB and several phenolic compounds reported in chickpea flour involve catalytic residues LYS343, GLU357 and ASP421 and HIS451, characteristic of the active site of tannases from L. plantarum. The importance of these amino acid residues was also highlighted in previous studies dealing with molecular docking (de Las Rivas et al, 2019;Rha et al, 2019). It has been reported that lysine, glutamic and aspartic acid and histidine residues found in tannases from Fusobacterium nucleatum may interact hydroxyl groups of ethyl gallate during molecular dynamics simulations (Mancheño et al, 2020), in agreement with chemical interactions determined in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The interactions between tannases from LAB and several phenolic compounds reported in chickpea flour involve catalytic residues LYS343, GLU357 and ASP421 and HIS451, characteristic of the active site of tannases from L. plantarum. The importance of these amino acid residues was also highlighted in previous studies dealing with molecular docking (de Las Rivas et al, 2019;Rha et al, 2019). It has been reported that lysine, glutamic and aspartic acid and histidine residues found in tannases from Fusobacterium nucleatum may interact hydroxyl groups of ethyl gallate during molecular dynamics simulations (Mancheño et al, 2020), in agreement with chemical interactions determined in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The examples include the Bactoferm range that contains the sakacin and pediocin that produce strains and is used in making cured dry meat and the fermented sausages and also the protective cultures of HOLDBAC. Moreover, it contains a mix of the bacteriocin to produce a strain that is used in protecting seafood, dairy products, and meat from moulds, yeast and Listeria (Rha et al 2019). In the current scenario, the novel bacteriocins that are potential as the food preservatives that include the plantaricyclin A, the circular bacteriocins that are produced by isolating the Lactobacillus Plantarum.…”
Section: Bacteriocins As Biological Food Preservativesmentioning
confidence: 99%